Requirement of Innate Immunity in Tumor-Bearing Mice Cured by Adoptive Immunotherapy Using Tumor-Draining Lymph Nodes - John Ammori; Khaled Hamzeh; Hallie Graor; Julian Kim (Journal of Immunology Research)
Background. The purpose of this study was to determine the cellular effectors of both the adoptively transferred cells and the tumor-bearing host that participate in the antitumor response to adoptive immunotherapy using culture-activated tumor-draining lymph nodes (TDLNs). Methods. TDLNs harvested from mice with 4T1 carcinoma cells were fractionated to derive the L-selectinlow subpopulation and activated ex vivo prior to in vitro cytokine release assays and adoptive transfer into BALB/c mice bearing 3-day established subcutaneous tumors. Tumor-bearing recipients were SCID (lacking T, B, and NK cells), Rag2 deficient (lacking T and B cells), and wild-type BALB/c mice. Results. Culture-activated L-selectinlow 4T1 TDLN from BALB/c mice secreted significant levels of interferon-gamma in response to 4T1 but not control tumor cells in vitro. CD4 cells within the adoptively transferred effector cell population contributed significantly to the antitumor effect in vivo. Culture-activated L-selectinlow TDLNs from BALB/c wild-type mice were able to cure Rag2 deficient but not SCID mice bearing 4T1 subcutaneous tumors, suggesting a requirement of NK cells within the innate immune system of the tumor-bearing host during the antitumor response. Conclusions. These results identify the cellular effectors involved in tumor regression following adoptive transfer and demonstrate the requirement for intact innate immunity within the tumor-bearing host.